Wired to Doubt: Why People Fear Vaccines and Climate Change and Mistrust Science - Dobson, Geoffrey P. (Frontiers in Medicine, 2022)
We all want to be right in our thinking. Vaccine hesitancy and global warming denial share much in common: 1) both are threats to personal, community and global health, 2) action is contingent on co-operation and social policy, and 3) public support relies on trust in science. The irony is, however, as the science has become more convincing, public opinion has become more divided. A number of early polls showed that ~70% of people supported COVID-19 vaccine use and global warming, ~20% adopted a wait-and-see approach, and ~10% were staunch objectors. Although these poll percentages are approximate, what factors are responsible for the differences in engagement, doubt and distrust? How can we reduce the consensus gap? One approach is to return to grass roots and provide a brief history of the issues, understand the difference between fact and opinion, truth and falsehood, the problem of certainty, and how scientific consensus is reached. To doubt is a healthy response to new information, and it too has a scientific basis. Doubt and distrust reside in that region of the brain called the dorsolateral prefrontal cortex, which is responsible for suppressing unwanted representations. Bridging the consensus gap requires shifting human thinking patterns from doubt to belief, and belief to action. Education and improved public messaging are key, and social media providers require urgent oversight or regulation to remove false and harmful/dangerous content from our digital lives. Delays to vaccinate and failure to reduce greenhouse gases will dramatically change the way we live. The new norm may be more deadly COVID variants, strained healthcare systems, extreme weather patterns, diminished food supply, damage to world’s economies and widespread global instability.